PENGEMBANGAN DESAIN PENDIDIKAN PROFESI GURU (PPG) PRA JABATAN PADA JURUSAN ILMU PENDIDIKAN SOSIAL (IPS) - Iwan Purwanto (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. This study aims to provide policy direction on how to develop PPG Pre-service programs for Social Sciences Teachers at the Department of Social Sciences Education. The design of the Pre-service PPG program for Social Sciences teachers, it is expected that the Social Sciences Education Department can propose to the government to be appointed and appropriate and be able to organize the Pre-service PPG Programs for Social Sciences Teachers. The method used in this research is the research and development (R&D) method, the process used to develop and validate educational products. The policy analysis, comparative studies, and then developing the Pre-service PPG program design for Social Sciences Teachers. After a rough development, consultations with education experts and PPG Pre-service implementers so that the PPG Regular Pre-Position governance is better organized. The next stage is the validation test d education experts, PPG Pre-service managers. The next stage is the revision stage of the design of the Regular Pre-service PPG program for Social Sciences Teachers, then the final stage is the documentation of the proposed Pre-service PPG programs for Social Sciences Teachers at the Department of Social Sciences Education. Development of the opening design of the PPG Pre-service IPS Study Program teacher at the Social Sciences Department of FITK UIN Syarif Hidayatullah Jakarta, in general has had a good preparedness, this is based on the provisions governing the opening of PPG Regular Pre-service Study Programs, including: (1) readiness to organize the PPG Study Program Regular Pre-service Study Program, namely institutions, human resources and facilities and infrastructure; (2) curriculum and learning system, namely determining the profile of PPG graduates in the field of study, formulation of CPL in the fields of PPG study, curriculum structure, learning systems and assessments in PPG study programs ;; (3) the financing system, and (4) quality assurance. Based on the above provisions the Department of Social Sciences Education in general can prepare themselves, only constrained student dormitories are still under construction and the most important thing is to prepare yourself to become a regular PPG Pre-service organizer in a religious ministry environment, while still providing opportunities for the LPTK to include characteristics that become its superiority.Abstrak. Penelitian ini ditujukan untuk memberikan arah kebijakan bagaimana pengembangan desain program PPG Pra Jabatan untuk Guru IPS pada Jurusan Pendidikan IPS. Desain program PPG Pra Jabatan untuk Guru IPS diharapkan Jurusan Pendidikan IPS bisa mengusulkan kepada pemerintah untuk ditunjuk dan layak serta mampu menyelenggarakan Program PPG Pra Jabatan untuk Guru IPS. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan (R&D) yaitu proses yang digunakan untuk mengembangkan dan mevalidasi produk pendidikan. Analisis kebijakan, studi banding, kemudian dilakukan pengembangan desain program PPG Pra Jabatan untuk Guru IPS. Setelah dilakukan pengembangan kasar, dikonsultasikan dengan pakar pendidikan dan para pelaksana PPG Pra Jabatan sehingga tatakelola PPG Pra Jabatan Reguler lebih tertata dengan baik. Tahap selanjutnya adalah uji validasi d pakar pendidikan, pengelola PPG Pra Jabatan. Tahap selanjutnya adalah tahap revisi desain program PPG Pra Jabatan Reguler untuk Guru IPS, kemudian tahap akhir adalah tahap pendokumentasian usulan program PPG Pra Jabatan untuk Guru IPS pada Jurusan Pendidikan IPS. Pengembangan desain pembukaan Program Studi PPG Prajabatan guru IPS pada Jurusan Pendidikan IPS FITK UIN Syarif Hidayatullah Jakarta, secara umum telah memiliki kesiapan yang baik hal ini didasarkan, pada ketentuan yang mengatur pembukaan Prodi PPG Prajabatan regular antara lain: (1) kesiapan penyelenggaraan Program Studi PPG Program Studi Prajabatan Regular, yaitu kelembagaan, SDM dan sarana dan prasarana;; (2) kurikulum dan sistem pembelajaran, yaitu penetapan profil lulusan bidang studi PPG, perumusan CPL bidang studi PPG, struktur kurikulum, sistem pembelajaran dan penilaian dalam program studi PPG;; (3) sistem pembiayaan;; dan (4) penjaminan mutu. Berdasarkan ketentuan diatas Jurusan Pendidikan IPS secara umum bisa mempersiapkan diri, hanya terkendala asrama mahasiswa yang masih dalam tahap pembangunan. Dengan demikian yang terpenting adalah mempersiapkan diri untuk menjadi penyelenggara PPG Prajabatan regular di lingkungan kemetrerian agama, dengan tetap memberikan kesempatan kepada LPTK memasukan ciri khas yang menjadi keunggulannya.